A Newer Form of Psycho-Spiritual Detachment to Support Those Suffering at Work. Issue 2 (3rd April 2018) - Devenish-Meares, Peter
ABSTRACT: Psychological detachment is useful to those who suffer workplace stress or burnout. However, some literature notes that people still ruminate problematically while away from work. To assist individual's sense-making and support meaningful detachment the research for the first time compares psychological detachment to a self-kindly form of spiritual detachment. The research using a bricolage-oriented approach draws on Weick's sense-making motif and Richard Rohr's spirituality. To assist the interdisciplinary approaches to suffering a preliminary conceptual model is suggested that combines theory and practical worker-centered choices although further work will be needed to establish its ongoing veracity.